A multiplex microarray lateral flow immunoassay device for simultaneous determination of five mycotoxins in rice - Saowalak Adunphatcharaphon; Oluwatobi Kolawole; Thanasat Sooksimuang; Waraporn Panchan; Wannee Wasuthep; Anuwut Petdum; Grit Pichayawaytin; Rungroj Jintamethasawat; Narusorn Doljirapisit; Armote Somboonkaew; Prae Noppakuadrittidej; Sudtida Kaew-amdee; et al. (npj Science of Food)
Abstract Co-occurrence of multiple mycotoxins is a growing global food safety concern due to their harmful effects on humans and animals. This study developed an eco-friendly sample preparation method and an innovative multiplex microarray-based lateral flow immunoassay, using a novel portable reader for on-site simultaneous determination of five regulated mycotoxins—aflatoxin B1, T-2 toxin, zearalenone, deoxynivalenol, and fumonisin B1 in rice. The eco-friendly and ultrafast extraction procedure utilizes a bio-based solvent. Principally, the microarray signals generated through a novel luminescent organic dye were captured to quantify mycotoxin levels in samples using a portable reader installed with a user-friendly interface. The assay demonstrates accurate detection and quantification of these mycotoxins, with recoveries ranging from 77% to 127%. Detection limits ranged from 0.56 to 1.89 μg/kg, which were well below their regulatory limits, with a relative standard deviation below 25%. This analytical system provides an on-site method for detecting multiple mycotoxins in rice.